2022
DOI: 10.7759/cureus.31054
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Parotitis in a 10-Week-Old Male

Abstract: We describe a case of parotitis associated with coronavirus disease 2019 (COVID-19) in a young male infant. His presenting symptom at the time of diagnosis of COVID-19 was unilateral facial swelling. He then developed upper respiratory infection symptoms and proceeded to recover over a period of about a month. Testing for other causes of parotitis was unrevealing. Other cases of COVID-19-associated parotitis have been presented in the literature, but this case is by far the youngest child noted, and is a usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
4
2
Order By: Relevance
“…Intriguingly, the mucin hypersecretion by the acinar cells observed here is not supported by the common effects in the oral cavity, reported by COVID-19 patients, such as salivary glands dysfunction and xerostomia [35,36,54]. Similar effects have also been associated with salivary gland ectasia [55], parotitis [56], sialadenitis [4,57], sialadenosis [19,58], as well as Sjögren's syndrome (SS) [59,60]. A study has demonstrated that the viral infection seems to induce an SS-like disease either in SARS-CoV-2-infected mice or in COVID-19 patients [59].…”
Section: Sars-cov-2 Induces Mecs Death and Acinar Hypertrophy: A Sial...contrasting
confidence: 66%
“…Intriguingly, the mucin hypersecretion by the acinar cells observed here is not supported by the common effects in the oral cavity, reported by COVID-19 patients, such as salivary glands dysfunction and xerostomia [35,36,54]. Similar effects have also been associated with salivary gland ectasia [55], parotitis [56], sialadenitis [4,57], sialadenosis [19,58], as well as Sjögren's syndrome (SS) [59,60]. A study has demonstrated that the viral infection seems to induce an SS-like disease either in SARS-CoV-2-infected mice or in COVID-19 patients [59].…”
Section: Sars-cov-2 Induces Mecs Death and Acinar Hypertrophy: A Sial...contrasting
confidence: 66%
“…Unlike other cases, the present patient had no preceding respiratory symptoms, which is atypical given that respiratory symptoms were present in most literature cases, albeit mild in some (27), highlighting the variable presentation of the disease. All patients had undergone neck ultrasounds.…”
Section: Discussioncontrasting
confidence: 52%
“…Measles, influenza, adenoviruses, herpes simplex virus, and parvovirus B‐19 can all cause acute parotitis as a secondary viral infection. Little is known about the incidence of enlarged salivary glands in children with COVID‐19 (Brehm et al, 2022 ; Likitnukul, 2022 ; Moca et al, 2023 ). The SARS‐CoV‐2 virus might be transmitted from the salivary glands to the respiratory or digestive systems.…”
Section: Discussionmentioning
confidence: 99%